Secondary Victimizations in Missing Child Events - Plass, Peggy S. (American journal of criminal justice, 2007)
This paper examines the incidence and nature of secondary victimizations (attempted and completed physical assault, sexual assault, and robbery) in a population of missing children (nonfamily abducted, family abducted, runaway/thrownaway, general/benign missing). Using data from the NISMART-2 studies, the following questions are addressed: How much secondary criminal victimization of children occurs in the context of missing children events, and what is the nature of this victimization? Are some categories/ types of missing children event more likely to result in secondary victimization than others? Is the risk for secondary victimization greater for some missing children than others (e.g., are age or race factors)? Are the outcomes of missing child events which include secondary victimizations different in significant ways from those which do not (more likely to be associated with harm for children or more likely to involve public resources like law enforcement)?